KONSEP KEADILAN EKOLOGI MENURUT ENSIKLIK LAUDATO SI ARTIKEL 159-162 DALAM PERSPEKTIF TEOLOGI PENCIPTAAN - Adry Yanto Saputra (Aggiornamento, 2022)
The focus of this paper is the responsibility of humans to the nature created by God. Human responsibility towards creation is a form of ecological justice. This paper draws from the encyclical Laudato Si 159-162, which is the core of the concept of justice that Pope Francis calls for to all human beings in the world. The concept of justice departs from the perspective of Creation Theology, namely the duty to care for and preserve nature. Based on the objectives to be achieved from this paper, namely the steps and attitudes of humans to create justice for the created world where humans live and live. The author sees so many people who don't care about the environment, causing a lot of damage and natural disasters. This writing method uses an analytical study of encyclicals and the teachings of creation theology. Through the concept of ecological justice, readers are increasingly aware of the importance of caring for and preserving nature, as a common home. Because of the consequences of the sin of the first human, people until now also have a strong will to exploit natural resources. From this paper, the findings on environmental problems are a return to human awareness to pay attention to human life now and in the future. Because every human action today has an impact on human life in the future. The contribution of the writing for the readers is to build a new awareness through the concept of ecological justice in the theology of creation.